2015
DOI: 10.7554/elife.05338.023
|View full text |Cite
|
Sign up to set email alerts
|

Author response: A library of MiMICs allows tagging of genes and reversible, spatial and temporal knockdown of proteins in Drosophila

Abstract: Here, we document a collection of ∼7434 MiMIC (Minos Mediated Integration Cassette) insertions of which 2854 are inserted in coding introns. They allowed us to create a library of 400 GFP-tagged genes. We show that 72% of internally tagged proteins are functional, and that more than 90% can be imaged in unfixed tissues. Moreover, the tagged mRNAs can be knocked down by RNAi against GFP (iGFPi), and the tagged proteins can be efficiently knocked down by deGradFP technology. The phenotypes associated with RNA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…For Dsk-and Dilp2-GAL4 expression analysis a fluorescent reporter (Etheredge et al, 2018) carrying pJFRC105-10XUAS-IVS-NLS-tdTomato in VK00040 (a gift from Barret D. Pfeiffer, Rubin lab, Janelia Research Campus) and pJFRC29-10XUAS-IVS-myr::GFP-p10 in attP40 (Pfeiffer et al, 2012) was used. For examining CCKLR-17D1 expression, a MiMIC reporter (Nagarkar-Jaiswal et al, 2015) (BL 61771;y[1] w[*] Mi{PT-GFSTF.2}CCKLR-17D1[MI03679-GFSTF.2]) was used. For aggression and qPCR assays, comparisons were made between equivalent genetic backgrounds.…”
Section: Materials and Methods Fly Stocks And Rearingmentioning
confidence: 99%
“…For Dsk-and Dilp2-GAL4 expression analysis a fluorescent reporter (Etheredge et al, 2018) carrying pJFRC105-10XUAS-IVS-NLS-tdTomato in VK00040 (a gift from Barret D. Pfeiffer, Rubin lab, Janelia Research Campus) and pJFRC29-10XUAS-IVS-myr::GFP-p10 in attP40 (Pfeiffer et al, 2012) was used. For examining CCKLR-17D1 expression, a MiMIC reporter (Nagarkar-Jaiswal et al, 2015) (BL 61771;y[1] w[*] Mi{PT-GFSTF.2}CCKLR-17D1[MI03679-GFSTF.2]) was used. For aggression and qPCR assays, comparisons were made between equivalent genetic backgrounds.…”
Section: Materials and Methods Fly Stocks And Rearingmentioning
confidence: 99%
“…Further co-staining with Fas3 and Tin antibodies, we found that Fas3 is highly expressed in Tin-positive CBs (Figure 3A), while at a much lower level in Svp-positive CBs. Confirmed through co-staining in both WT and endogenous Ten-m::GFPtagged embryos (MiMIC-Ten-m::GFP) (Nagarkar-Jaiswal et al, 2015), Ten-m expression shows a complementary expression pattern to Fas3, with relatively higher expression in Svp-positive CBs than Tin-positive CBs (Figures 3B, S3D, and S3D 0 ).…”
Section: Candidate Screening Identified Differential Expression Of Fas3 and Ten-m In The Heartmentioning
confidence: 70%
“…We visualised Side at this stage using the GFP-exon trap line Mi00149-GFSTF (Nagarkar-Jaiswal et al, 2015), hereafter called SideGFP Mi00149 , that fuses with the cytoplasmic domain of Side to GFP at amino acid position 918 and does not disrupt protein function (see section Materials and Methods, Supplementary Figure 3). SideGFP Mi00149 was predominantly expressed in central discs areas (leg disc proper), but overall, it did not seem to reflect any ordered cell arrangements (Figures 1A,E).…”
Section: Resultsmentioning
confidence: 99%
“…Since Side protein is no longer detectable in late embryos using immunostainings (Sink et al, 2001;Siebert et al, 2009), we wanted to cheque if it is re-expressed during metamorphosis or if it is functionally replaced by one of its paralogs. To examine its postembryonic expression, we took advantage of a fluorescent exon-trap line that fuses GFP with the cytoplasmic domain of endogenous Side (Nagarkar-Jaiswal et al, 2015). In leg imaginal discs, Side was already expressed in Zfh1-positive adult muscle precursors in late third instar larvae, when adult motor axons begin to grow out of the CNS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation